Colorectal Cancer Chemotherapy: The Evolution of Treatment and New Approaches - M. McQuade, Rachel; Stojanovska, Vanesa; C. Bornstein, Joel; Nurgali, Kulmira (Current Medicinal Chemistry, 2017)
Colorectal cancer (CRC) is one the greatest contributors to cancer related mortality. Although 5 year survival rate for patients at the early stage of CRC (stages I and II) is above 60%, more than 50% of patients are diagnosed at or beyond stage III when distant metastasis has already occurred, in which case 5 year survival rate drops to 10%. Chemotherapeutic intervention coupled with surgery is the backbone of metastatic CRC treatment and the only means of enhanced survival. For decades following its discovery, an antimetabolite 5-fluorouracil (5-FU) was the only chemotherapeutic agent available to successfully improve 12 month survival in CRC patients. Treatment of metastatic CRC has been considered palliative for many years; aiming to increase the duration and quality of the patient's remaining life, with little hope of cure, highlighting the need for novel DNA and RNA targeted therapies in the treatment of CRC. Over the last several decades, combinations of several chemotherapeutic agents have been incorporated into routine clinical practice. Combination regimes incorporating irinotecan, a semisynthetic inhibitor of topoisomerase, oxaliplatin, a third-generation platinum compound that causes mitotic arrest via the formation of DNA adducts, and capecitabine, a 5-FU prodrug, are now all established options for use as first-line, second-line and sequential treatment of CRC. This review provides a brief overview of the evolution of CRC chemotherapy as well as new and emerging treatment options.
Keywords: cisplatin and oxaliplatin